IMPACTS OF ANATOMICAL REVIEW ON A CORPSE FROM THE PERSPECTIVE OF MEDICAL STUDENTS: : AN EXPERIENCE REPORT (REMUNOM, 2024)
This experience report discusses a short course entitled Anatomical Review in the Cadaver. The activity was carried out during the X Academic Week of Medicine at the Faculty of Medicine of Mucuri, at the Federal University of Vales Jequitinhonha and Mucuri in Teófilo Otoni-MG, under the organization of the League of Applied Morphofunctional Sciences. This mini-course aimed to provide participants with a practical review of clinically relevant anatomical structures through direct contact with cadavers, in addition to addressing ethical and technical aspects of the use of human bodies for study purposes. The objective of the report is to record and describe the impact of the experience on learning human anatomy from the perspective of the students who participated in the short course. Through the application of perception forms, the impressions of the students taking the course and the running team about the mini-course were collected. The analysis of the perception questionnaires highlighted the significant contribution of the mini-course to the evolution and consolidation of anatomical learning and to the ethical awareness of future medical professionals. Furthermore, the mini-course strengthened the understanding of the macroscopic morphology of the human body, it also allowed visualization of the anatomical relationships between body structures and the observation of anatomical variations in situ.